Self‐assembling of three rare structurally various homomultinuclear CuII complexes derived from a bis(salamo)‐based multioxime ligand. Issue 5 (22nd September 2021) - Li, Peng; Zhang, Ting; Li, Li-Li; Dong, Wen-Kui
Abstract : Three rare structurally different homometal multinuclear Cu II bis(salamo)‐based complexes have been successfully synthesized and structurally characterized. Due to the existence of different solvent molecules and counter anions, the structures and interactions of the three complexes are influenced. Abstract : A family of rare structurally different homometal multinuclear Cu II bis(salamo)‐based complexes, [Cu4 ( L )2 (MeOH)2 ](ClO4 )2 ·2MeOH (1), [Cu4 ( L )2 (EtOH)2 ](NO3 )2 ·2EtOH (2) and [Cu2 (H L )(EtOH)Br2 ]·CHCl3 (3), has been successfully synthesized by the reactions of cupric salts with a bis(salamo)‐based multidentate chelate ligand (H3 L ). The salamo‐based ligand [ R ‐CH=N—O—(CH2 ) n —O—N=CH— R ] is a new type of salen‐based analog. Complexes (1) and (2) are isostructural structures, and crystallize in monoclinic space group P 21 / n with centrosymmetric spiral structures, where the main structures contain two fully deprotonated ligand ( L ) 3− units, a charged tetranuclear Cu II folding center and two coordinated solvent molecules. Complex (3) crystallizes in monoclinic space group Cc and consists of two Cu II cations, one incompletely deprotonated ligand (H L ) 2− unit and one coordinated ethanol molecule, and forms a novel homo‐binuclear Cu II complex structure due to Br − counter anions. Complexes (1)–(3) have zero‐dimensional cluster‐based structures and are further assembled into three‐dimensional frameworks via intermolecular interactions. Because of the different solvents and counter anions which have a significant influence on the structures of complexes (1)–(3), the interactions were quantitatively evaluated by Hirshfeld surfaces analyses. Complexes (1)–(3) have been characterized by elemental analyses, IR spectra, UV–vis spectra and X‐ray crystallography analyses. In addition, fluorescence properties are evaluated and DFT calculations are performed.